Assessment of Occupational Stress among Nurses' at Baghdad Medical Complex Hospitals in Baghdad City, Iraq - Obaid, RaadKhamees; Qassim, Wissam Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
Background: Occupational stress is a major and complex issue in working environments. It is among the major reasons for decreased earnings in organizations and its effects on employees are physical and psychological. Work stress is far more important in health care field, as the provision of health services is very laborious and high - risk.Amis the study aimed to assess occupational stress among nurses and Find out the relationship between sociodemographic characteristics of the nurses and occupational stress in the Baghdad Medical Complex.Methodology: A descriptive study is conducted to assess the occupational stress among nurses’ at Baghdad Medical Complex Hospitals in Baghdad City from 1st October. 2019 to 4th Apr 2020.A multistage is a sample of(316) out by (1653) nurses. The sample chooses by cluster sampling. Baghdad Medical complex, which The findings of the current study revealed that the level of occupational stress among nurses was measured using a questionnaire survey and professional stress scale.Results: In this study, hospital nurses reported moderate and mild stress levels. The main occupational stressors for nurses were a poor attitude of a doctor, a work in stressful departments (emergency / ICU), insufficient income, excess work, time pressure and labor with insufficient meal and rest. Stress reduces skills of attention, focus, judgment and decision making. Recomndiation:The study recommended that the Medical City Complex Hospital's in Baghdad should focus on the importance of occupational stress among nurses and attention to the importance of organizational commitment and its impact on occupational stress to reach the provision of quality health care.